2022
DOI: 10.1002/jbt.23199
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning/ischemic postconditioning alleviates anoxia/reoxygenation injury via the Notch1/Hes1/VDAC1 axis

Abstract: Ischemic preconditioning (IPC), and ischemic postconditioning (IPost) have a significant protective effect on myocardial ischemia/reperfusion (MI/R) injury by alleviating oxidative stress and mitochondrial disturbances, although the underlying molecular mechanisms are unclear. The study was to demonstrate that cardioprotection against anoxia/reoxygenation (A/R) injury is transduced via the Notch1/Hes1/VDAC1 signaling pathway. Using mass spectrometry and tandem affinity purification (TAP), to screen for differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…As presented in a previous study 21 , an in vitro MIRI model (anoxia/reoxygenation injury model) was established as follows: First, H9c2 cardiomyocytes were cultured in anoxia lipid (CaCl 2 1.0 mM, HEPES 20 mM, KCl 10 mM, MgSO 4 1.2 mM, NaCl 98.5 mM, NaH 2 PO 4 0.9 mM, NaHCO 3 6 mM, and sodium lactate 40 mM, pH 6.8) at 95% N 2 and 5% CO 2 for 3 h. Subsequently, reoxygenation lipid (CaCl 2 1.0 mM, glucose 5.5 mM, HEPES 20 mM, KCl 5 mM, MgSO 4 1.2 mM, NaCl 129.5 mM, NaH 2 PO 4 0.9 mM, and NaHCO 3 20 mM, pH 7.4) was applied to mimic reperfusion, and H9c2 cardiomyocytes were cultured in 95% O 2 and 5% CO 2 for 2 h (normal conditions).…”
Section: Methodsmentioning
confidence: 52%
“…As presented in a previous study 21 , an in vitro MIRI model (anoxia/reoxygenation injury model) was established as follows: First, H9c2 cardiomyocytes were cultured in anoxia lipid (CaCl 2 1.0 mM, HEPES 20 mM, KCl 10 mM, MgSO 4 1.2 mM, NaCl 98.5 mM, NaH 2 PO 4 0.9 mM, NaHCO 3 6 mM, and sodium lactate 40 mM, pH 6.8) at 95% N 2 and 5% CO 2 for 3 h. Subsequently, reoxygenation lipid (CaCl 2 1.0 mM, glucose 5.5 mM, HEPES 20 mM, KCl 5 mM, MgSO 4 1.2 mM, NaCl 129.5 mM, NaH 2 PO 4 0.9 mM, and NaHCO 3 20 mM, pH 7.4) was applied to mimic reperfusion, and H9c2 cardiomyocytes were cultured in 95% O 2 and 5% CO 2 for 2 h (normal conditions).…”
Section: Methodsmentioning
confidence: 52%
“…As described in previous studies ( 20 , 21 ), the cell A/R liquid method was applied to establish an in vitro A/R model. H9c2 cells were incubated in anoxia medium (CaCl 2 1.0, HEPES 20.0, KCl 10.0, MgSO 4 1.2, NaCl 98.5, NaH 2 PO 4 0.9, NaHCO 3 6.0 and sodium lactate 40.0 mM, pH 6.8) and 95% N 2 and 5% CO 2 at 37°C for 3 h. Reoxygenation medium (CaCl 2 1.0, glucose 5.5, HEPES 20.0, KCl 5.0, MgSO 4 1.2 mM, NaCl 129.5, NaH 2 PO 4 0.9 and NaHCO 3 20.0 mM, pH 7.4) was used to simulate IRI and cells were incubated under 95% O 2 and 5% CO 2 at 37°C for 2 h.…”
Section: Methodsmentioning
confidence: 99%
“…As a key component of the outer membrane of mitochondria, VDAC1 participates in the transportation of metabolites, nucleotides and ions ( 16 ). Moreover, previous studies have shown that expression of VDAC1 is upregulated and indicates more severe myocardial damage after anoxia/reoxygenation (A/R) treatment ( 18 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notch1 also mediates cardioprotection due to IPC by regulating STAT3 phosphorylation (94). The Notch1/Hes1 signaling pathway is activated by IPC/IPost and has been confirmed to directly downregulate the expression of voltage-dependent anion channel 1 and relieve MI/RI (95).…”
Section: Role Of Notch1 Signaling In Ischemia-reperfusion Injurymentioning
confidence: 97%